Differential Proinflammatory Signature in Vestibular Migraine and Meniere Disease - Flook, Marisa; Frejo, Lidia; Gallego-Martinez, Alvaro; Martin-Sanz, Eduardo; Rossi-Izquierdo, Marcos; Amor-Dorado, Juan Carlos; Soto-Varela, Andres; Santos-Perez, Sofia; Batuecas-Caletrio, Angel; Espinosa-Sanchez, Juan Manuel; Pérez-Carpena, Patricia; Martinez-Martinez, Marta; et al. (Frontiers in Immunology, 2019)
Vestibular Migraine (VM) and Meniere’s Disease (MD) are episodic vestibular syndromes defined by a set of associated symptoms such as tinnitus, hearing loss or migraine features during the attacks. Both conditions may show symptom overlap and there is no biological marker to distinguish them. Two subgroups of MD patients have been reported, according to their IL-1β profile. Therefore, considering the clinical similarity between VM and MD, we aimed to investigate the cytokine profile of MD and VM as a means to distinguish these patients. We have also carried out gene expression microarrays and measured the levels of 14 cytokines and 11 chemokines in 129 MD patients, 82 VM patients and 66 healthy controls. Gene expression profile in peripheral blood mononuclear cells (PBMC) showed significant differences in MD patients with high and low basal levels of IL- 1β and VM patients. MD patients with high basal levels of IL- 1β (MDH) had overall higher levels of cytokines/chemokines when compared to the other subsets. CCL4 levels were significantly different between MDH, MD with low basal levels of IL- 1β (MDL), VM and controls. Logistic regression identified IL- 1β, CCL3, CCL22 and CXCL1 levels as capable of differentiating VM patients from MD patients (area under the curve=0.995), suggesting a high diagnostic value in patients with symptoms overlap.